Measurement of cerebral blood volume dynamics during volitional swallowing using functional near-infrared spectroscopy: An exploratory study. (19th February 2015) - Inamoto, Kyoko; Sakuma, Shigemitsu; Ariji, Yoshiko; Higuchi, Naoya; Izumi, Masahiro; Nakata, Kazuhiko
Highlights: We examined cerebral blood volume dynamics during volitional swallowing. We used a 52-channel functional near-infrared spectroscopy system. Increased oxy–Hb was found in the bilateral sensorimotor cortex. Increased oxy–Hb was found in the temporal gyrus. Abstract: The aim of this study was to examine cerebral blood volume dynamics during volitional swallowing using multi-channel functional near-infrared spectroscopy (fNIRS) to understand the basic cortical activation patterns. Fifteen volunteers (age, 26.5 ± 1.3 years, mean ± SD) performed volitional swallowing of a 5-ml bolus of water as a task. A 52-channel fNIRS system was used for measuring oxy–Hb levels. We determined the oxy–Hb concentration changes in each channel by calculating the differences between rest and task oxy–Hb levels. Differences in rest and task data were assessed using a paired- t test ( p < 0.05). A significant increase in oxy–Hb was found in 21 channels. The cortical regions that exhibited increased oxy–Hb concentration included the bilateral precentral gyrus, postcentral gyrus, inferior frontal gyrus, superior temporal gyrus, middle temporal gyrus, and supramarginal gyrus. These data provide the first description of cortical activation patterns during volitional swallowing using fNIRS, which will be useful for the evaluation of dysphasia and the effects of the rehabilitation.